2003
DOI: 10.1097/00000374-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

NPY leu7pro and Alcohol Dependence in Finnish and Swedish Populations

Abstract: Pro7 does not seem to be associated with a diagnosis of alcoholism in Caucasian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…45 A functional polymorphism in the human NPY (Leu7Pro) resulting in increased NPY release from sympathetic nerves is associated with characteristics of metabolic syndrome and it has been suggested that the Pro7 allele is associated with an increased risk for alcohol dependence, a common comorbid disorder of ADHD. 46 In the rodent model, central administration or overexpression of NPY produces a profound increase in food intake, whereas a reduction of NPY results in a decrease (for review see Karl and Herzog 45 ). Food deprivation upregulates NPY in the arcuate nucleus of the hypothalamus, and repeated administration of NPY induces obesity.…”
Section: Discussionmentioning
confidence: 99%
“…45 A functional polymorphism in the human NPY (Leu7Pro) resulting in increased NPY release from sympathetic nerves is associated with characteristics of metabolic syndrome and it has been suggested that the Pro7 allele is associated with an increased risk for alcohol dependence, a common comorbid disorder of ADHD. 46 In the rodent model, central administration or overexpression of NPY produces a profound increase in food intake, whereas a reduction of NPY results in a decrease (for review see Karl and Herzog 45 ). Food deprivation upregulates NPY in the arcuate nucleus of the hypothalamus, and repeated administration of NPY induces obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a high comorbidity of alcoholism, addiction, and cognitive dysfunction with various psychiatric conditions (3). There are several clinical studies investigating the cerebrospinal fluid (CSF) and plasma NPY concentrations in psychiatric disorders such as anxiety disorders, depression, stress related disorders, alcohol dependence, and eating disorders (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Among these are monoaminergic genes involved in brain reward pathways and serotonergic genes involved in impulse control and anxiety traits (for review, see Enoch and Goldman 1 ). More recently, on the basis of animal studies, an involvement has been suggested for neuropeptide Y (NPY), 2 but human findings have been inconsistent, 3,4 possibly due to the methodological difficulties involved, and due to the limited quantitative contribution of individual loci in the complex trait of alcoholism.…”
Section: Introductionmentioning
confidence: 99%